The development of students industrial training information system (FBM-STIS): impact towards process efficiency / Norhidayah Mohd Rashid ...[et al.] - Mohd Rashid, Norhidayah; Ma'amor, Hairunnisa; Badrolhisam, Nur Idayu; Humaidi, Norshima; Shariff, Siti Halijjah; Kasdi @ Abd Rahim, Saiful Azmir (Universiti Teknologi MARA, 2021)
Faculty of Business and Management has developed Student Industrial Training Information System (FBM-STIS) to facilitate the faculty pertaining to student internship placement in line with Industrial Revolution 4.0 (IR 4.0) emerged worldwide. Internship is a must for most undergraduate programs and it is carried out in the final semester. Owing to the complexity of the process, FBM-STIS is hoped to provide ease and accurate information to the students and FBM administrative staff. FBM-STIS also enhances efficiency through the reduction of time for students to receive the Confirmation Letter (CL), and support Green Nation program through its paperless initiatives and reduction of carbon emission since students' physical presence is not needed at the faculty. Above all, it assists UiTM in its strategy to 'Jana and Jimat' in that, FBM-STIS is able to reduce operational cost. With the latest technologies, the study hopes the system match with the preferences of Generation Z who are more IT literate that favor simple and prompt process and feedback.